2019
DOI: 10.1016/j.physa.2019.121301
|View full text |Cite
|
Sign up to set email alerts
|

Are disaggregate industrial returns sensitive to economic policy uncertainty

Abstract: This study investigates the impact of economic policy uncertainty on disaggregate US sector based returns. Our work is motivated by the presence of non-linear relationship between US economic policy uncertainty and equity returns of sampled US sectors. The paper uses weekly data from January 1995 to December 2015 for all the return indices and economic policy uncertainty data mainly based on policy issues, provision set for the US federal tax code and disagreement among economic forecasters. Our results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 78 publications
1
5
0
2
Order By: Relevance
“…Therefore, economic policy uncertainty (EPU) is attributable to multiple factors, including uncertainty in monetary, fiscal, economic, social, political and regulatory policies. However, uncertainty can elicit a strong reaction from macroeconomic factors mainly contributes by government policymakers due to electoral outcomes or uncertain regimes (Baker et al, 2016;Rehman et al, 2019). A nonlinear ARDL approach is developed by Kocaarslan et al (2020) to investigate the presence of asymmetric interactions among oil prices, uncertainty interest rate and unemployment.…”
Section: Evidence In Developed Countriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, economic policy uncertainty (EPU) is attributable to multiple factors, including uncertainty in monetary, fiscal, economic, social, political and regulatory policies. However, uncertainty can elicit a strong reaction from macroeconomic factors mainly contributes by government policymakers due to electoral outcomes or uncertain regimes (Baker et al, 2016;Rehman et al, 2019). A nonlinear ARDL approach is developed by Kocaarslan et al (2020) to investigate the presence of asymmetric interactions among oil prices, uncertainty interest rate and unemployment.…”
Section: Evidence In Developed Countriesmentioning
confidence: 99%
“…However, uncertainty can elicit a strong reaction from macroeconomic factors mainly contributes by government policymakers due to electoral outcomes or uncertain regimes (Baker et al. , 2016; Rehman et al. , 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results suggest that increasing EPU hinders equity returns except UK and France. In a more recent work, Rehman, Asghar, and Hussain (2019) examine the sensitivity of US sectoral returns to economic policy uncertainty and find that IT, utilities, industrials and telecommunications sector highlight no changes to US EPU.…”
Section: Economic Policy Uncertainty and The Stock Marketmentioning
confidence: 99%
“…Economic agents have their beliefs about possible approaches of the government's industrial policy, subsidies or taxes that will integrate future economic policy. In [22] it is shown that information technology, utilities, industrial and telecommunication sectors remain mostly insensitive to changes in the US economic policy uncertainty. However, financial and consumer discretionary sectors show a significant long run asymmetric relationship with the economic policy uncertainty.…”
Section: 21mentioning
confidence: 99%